Diagnósticos de enfermagem em pacientes com risco de lesão por pressão em unidades de terapia intensiva - ALMEIDA, Alana Gomes de Araújo (2021)
This study aimed to determine the overall picture of nursing diagnoses presented by patients at risk of pressure injury in an intensive care unit (ICU). This is a cross sectional study, with an analytical approach, developed from February 2020 to January 2021 in a reference tertiary hospital located in a capital city in the northeast of Brazil. The sample consisted of 105 patients who were in the first 48 hours of in the ICU, they were 18 years of age or older and had a risk of pressure injury according to the Braden scale. For data collection, the instrument proposed by Ramalho Neto, Fontes and Nóbrega (2013) was adapted in order to cover the 24 nursing diagnoses required in this research. To assess the link between nursing diagnoses and clinical and sociodemographic variables, the tests applied were: the Pearson's Chi-square test or the Fischer's exact test. The last one was used in situations in which the expected frequencies were less than five. For statistical significance, a level of 5% (p <0.05) was adopted. The results show a relation between clinical and sociodemographic variables with the evaluated nursing diagnoses: unbalanced diet: insufficient to body needs; Obesity; Overweight; Deficient volume of liquids; Diarrhea; Inadequate urinary elimination; Impaired gas exchange; Decreased physical mobility; Impaired mobility in the hospital bed; Ineffective breathing pattern; Acute confusion; Impaired verbal communication; Impaired skin integrity. Regarding the analysis to verify the association of nursing diagnoses with the Braden scale, the data obtained was statistically significant for: Decreased physical mobility, Unilateral neglect, Acute confusion and Impaired verbal communication. In the analysis of the association between the diagnoses and the components of the Braden scale, a statistically significant association was obtained for the components: Sensorial perception; Nutrition and Friction and shear. These results emphasize that the risk of developing pressure injury is a multi-causal event, therefore, understanding these causes allows the nurse to conduct their assistance with the elaboration of a care plan that incorporates all the situations in the development of the pressure injury.